P1348EFFECT OF CILOSTAZOL ON ARTERIOVENOUS FISTULA IN HEMODIALYSIS PATIENTS. (6th June 2020) - JEON, JAE WAN; Ham, Young Rok; Kim, Haeri; Choi, Wonjung; Na, Ki Ryang; CHOI, DAE EUN; Lee, Kang Wook
Abstract: Background and Aims: Permanent vascular access is important in patients requiring hemodialysis. However, among patients requiring hemodialysis, even if arteriovenous fistula surgery is performed, many are unable to undergo hemodialysis with vascular access due to maturation failure. Method: Using 194 patients who underwent arteriovenous fistula surgery, a cilostazol group (n = 107) and a control group (n = 87) were compared and analyzed for the occurrence of vascular complications. Results: In the cilostazol group, there were less vascular complications (36.4% vs. 52.9%; p = 0.022), especially maturation failure (2.8% vs. 11.5%; p = 0.016). However, there was no significant difference between the cilostazol group and control group regarding percutaneous transluminal angioplasty (PTA) requirement nor frequency and interval to PTA after vascular surgery. The frequency of reoperations due to vascular injury after the start of hemodialysis after maturation was also significantly lower in the cilostazol group. Conclusion: These results suggest that vascular access patients may benefit from postoperative cilostazol therapy.